Arbuscular mycorrhizal trees influence the latitudinal beta-diversity gradient of tree communities in forests worldwide - Zhong, Yonglin; Chu, Chengjin; Myers, Jonathan A; Gilbert, Gregory S; Lutz, James A; Stillhard, Jonas; Zhu, Kai; Thompson, Jill; Baltzer, Jennifer L; He, Fangliang; LaManna, Joseph A; Davies, Stuart J; et al. (Nature communications, 2021)
Arbuscular mycorrhizal (AM) and ectomycorrhizal (EcM) associations are critical for host-tree performance. However, how mycorrhizal associations correlate with the latitudinal tree beta-diversity remains untested. Using a global dataset of 45 forest plots representing 2,804,270 trees across 3840 species, we test how AM and EcM trees contribute to total beta-diversity and its components (turnover and nestedness) of all trees. We find AM rather than EcM trees predominantly contribute to decreasing total beta-diversity and turnover and increasing nestedness with increasing latitude, probably because wide distributions of EcM trees do not generate strong compositional differences among localities. Environmental variables, especially temperature and precipitation, are strongly correlated with beta-diversity patterns for both AM trees and all trees rather than EcM trees. Results support our hypotheses that latitudinal beta-diversity patterns and environmental effects on these patterns are highly dependent on mycorrhizal types. Our findings highlight the importance of AM-dominated forests for conserving global forest biodiversity.
Keywords: distribuce rostlin; Biodiversity; Mycorrhizae; stromy; Plant Dispersal; interakce mikroorganismu a hostitele; biodiverzita; půdní mikrobiologie; Trees; Host Microbial Interactions; lesy; Soil Microbiology; mykorhiza; Forests